English use anxiety, motivation, self-efficacy, and their predictive effects on Chinese top university students’ English achievements - Wu, Xia; Yang, Huameng; Liu, Junxia; Liu, Ziyu (Frontiers in Psychology, 2022)
The present study examined English use anxiety, motivation, self-efficacy, use of English and their predictive effects on top university students’ English achievements. Two hundred and twenty-three students of the Top-Notch Students of Basic Disciplines Training Program in a top Chinese university answered a battery of questionnaires, which consisted of the 8-item English Use Anxiety Questionnaire, the 5-item Motivational Self-Talk Questionnaire, the 3-item Self-Efficacy Questionnaire, the 19-item Language Learning Orientations Questionnaire, and a Background Information Questionnaire. Analyses of the data revealed the following major findings: 1) the participants had a low level of extrinsic motivation-introjected regulation, a low-to-medium level of English use anxiety, extrinsic motivation-external regulation, intrinsic motivation-knowledge, and a medium-to-high level of motivational self-talk, self-efficacy, extrinsic motivation-identified regulation, intrinsic motivation-accomplishment and intrinsic motivation-stimulation, 2) use of English anxiety and language learning orientation were generally significantly negatively correlated with each other, and significantly correlated with other measured variables, 3) use of English anxiety and intrinsic motivation-knowledge significantly predicted the participants English achievements, measured both by standardized test scores and self-rated overall English proficiency, and 4) use of English and self-efficacy mediated the effects of English use anxiety and language learning orientations on the participants’ English achievements. These findings further pinpoint the importance of anxiety and motivation in second/foreign language learning.